Murder at the PTA - Hollis, Lee (Hollis, Lee. Maya & Sandra mysteries, 2020)
"Someone is trying to turn Portland High into a school for scandal with a gossipy website called Dirty Laundry. The latest target of ruinous rumors is newly elected PTA president Sandra Wallage. After a heated meeting with outraged parents, Sandra runs into fellow school mom and private investigator Maya Kendrick, who's discovered the person behind the website. But when the women storm into the venomous gossip columnist's office they find a lifeless body--along with a confession. Although the police rule the death a suicide, Maya suspects an injured party hung the Dirty Laundry creator out to dry. Maya already has a PI partner--but she's pregnant, and sonograms and stakeouts tend to conflict. So when Sandra volunteers for a crash course in sleuthing, Maya accepts the help. But as these unlikely partners study the clues, a killer plans to teach them a lesson"--Page 4 of cover.